Factors affecting intentions to use banking services in Yemen - Alqasa, Khaled; Md Isa, Filzah; Othman, Siti Norezam (2013)
The issue of attracting customers’ usage of banking services has been solved in many countries. However, in Yemen, it is still unpredictable, where most of people do not use bank services to facilitate their financial needs. Therefore, it has caused a real problem in the Yemeni economy. Consequently, this research targets to close the gap by investigating the factors influencing Yemeni's consumers who possibly differ from consumers in the developed countries in terms of their psychological, cultural and behaviour to use the banking system. Data were collected through questionnaires from university students and analyzed by SPSS version 17. Hypotheses were tested by means of factor analysis, correlation and regression analysis. The study highlighted that the relationship between, service quality, banking Legal framework, bank advertisement are significant and positive on behavioural intention except cultural belief where it was significant but played a negative role in using the banking system in Yemen.